Soil physico-hydrical properties resulting from the management in Integrated Production Systems - Auler, André; Miara, Simone; Pires, Luis; Fonseca, Adriel; Barth, Gabriel (Revista Ciência Agronômica, 2014)
Anthropic action, such as the soil use and management systems, promote changes in the soil structure. These changes might hamper the development of plants in soil management practices that involve its mobilization, and the negative effects might be increased due to intensive use. The aim of this study was to evaluate the physico-hydrical properties of a Haplohumox in integrated production systems under different soil managements. The soil superficial (0.0-0.10 m) and sub-superficial (0.10-0.20 m) layers were evaluated in the different systems: conventional tillage (CT), minimum tillage (MT), no-tillage (NT) and chiseled no-tillage (CNT), taking into consideration the annual ryegrass cropped for different uses [cover crop (C), grazing (G) and silage (S)] during the winter. Soil bulk density (Db), total porosity (TP), macro (Ma) and microporosity (Mi), water retention curves (SWRC) and water retention due to pore size (r) were determined. The annual ryegrass used as C produced lower Db and Mi and higher TP and Ma in CT, MT and CNT systems. No difference was verified between G and S in any of the management systems or soil layers. The superficial layer SWRC presented similar behavior regarding CT, MT and CNT. Under NT, C resulted in higher water retention. However, G and S provided higher water retention due to the pore size in this system.